Strategies to Improve Follow-up After Positive Fecal Immunochemical Tests in a Community-Based Setting: A Mixed-Methods Study. Issue 2 (February 2019) - Selby, Kevin; Jensen, Christopher D.; Zhao, Wei K.; Lee, Jeffrey K.; Slam, Arielle; Schottinger, Joanne E.; Bacchetti, Peter; Levin, Theodore R.; Corley, Douglas A.
Abstract : OBJECTIVES: The effectiveness of fecal immunochemical test (FIT) screening for colorectal cancer depends on timely colonoscopy follow-up of positive tests, although limited data exist regarding effective system-level strategies for improving follow-up rates. METHODS: Using a mixed-methods design (qualitative and quantitative), we first identified system-level strategies that were implemented for improving timely follow-up after a positive FIT test in a large community-based setting between 2006 and 2016. We then evaluated changes in time to colonoscopy among FIT-positive patients across 3 periods during the study interval, controlling for screening participant age, sex, race/ethnicity, comorbidity, FIT date, and previous screening history. RESULTS: Implemented strategies over the study period included setting a goal of colonoscopy follow-up within 30 days of a positive FIT, tracking FIT-positive patients, early telephone contact to directly schedule follow-up colonoscopies, assigning the responsibility for follow-up tracking and scheduling to gastroenterology departments (vs primary care), and increasing colonoscopy capacity. Among 160, 051 patients who had a positive FIT between 2006 and 2016, 126, 420 (79%) had a follow-up colonoscopy within 180 days, including 67% in 2006–2008, 79% in 2009–2012, and 83% in 2013–2016 ( P < 0.001). Follow-up within 180 days in 2016 varied moderately across service areas, between 72% (95% CI 70–75) and 88% (95% CI 86–91), but there were no obvious differences in the pattern of strategies implemented in higher- vs lower-performing service areas. CONCLUSIONS: The implementation of system-level strategies coincided with substantial improvements in timely colonoscopy follow-up after a positive FIT. Intervention studies are needed to identify the most effective strategies for promoting timely follow-up.